2018
DOI: 10.1177/0309524x18780382
|View full text |Cite
|
Sign up to set email alerts
|

Monte Carlo methods to include the effect of asymmetrical uncertainty sources in wind farm yield assessment

Abstract: This article presents a method for incorporating the effect on expected annual energy production of a wind farm caused by asymmetric uncertainty distributions of the applied losses and the nonlinear response in turbine production. The necessity for such a correction is best illustrated by considering the effect of uncertainty in the oncoming wind speed distribution on the production of a wind turbine. Due to the shape of the power curve, variations in wind speed will result in a skewed response in annual energ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Fazelpour et al [12] used the Windographer software [13] to perform wind resource analysis but they did not have access to the real wind data from LIDAR. Gleim et al [14] dealt with uncertainties associated with the calculation of annual energy production using the MCS approach. They found that the wind speed uncertainty may cause error between 0.5% and 1.5% in estimation of annual energy production.…”
Section: Introductionmentioning
confidence: 99%
“…Fazelpour et al [12] used the Windographer software [13] to perform wind resource analysis but they did not have access to the real wind data from LIDAR. Gleim et al [14] dealt with uncertainties associated with the calculation of annual energy production using the MCS approach. They found that the wind speed uncertainty may cause error between 0.5% and 1.5% in estimation of annual energy production.…”
Section: Introductionmentioning
confidence: 99%